Peran Kepribadian Tangguh terhadap Kebijaksanaan pada Karyawan di Kota Surakarta - Hapsari, Maharani Tyas Budi; Badriyah, Nurul (Universitas Muhammadiyah Metro, 2024)
This study aims to analyze the role of hardiness personality on wisdom in middle-aged employees in the city of Surakarta. The hypothesis in this study is that a hardiness personality has a positive effect on wisdom in middle-aged employees in the city of Surakarta. There were 166 research subjects consisting of 80 men and 86 women. This study used a wisdom scale with a reliability of 0.853 and a hardiness personality scale with a reliability of 0.926. The results showed that a hardiness personality significantly affected the wisdom of teaching staff in Surakarta with an effective contribution of 10.1%. The results can be seen from the regression coefficient of hardiness personality on wisdom 0.318 with a p-value <0.05. Thus, the hypothesis in this study is accepted. Overall, this study explains the wisdom of middle-aged employees in the city of Surakarta.